Handbook of Military Sciences: (Anders McD Sookermany (ed.)) - O'Neil, Johnny (Scientia Militaria - South African Journal of Military Studies, 2026)
Handbook of Military Sciences edited by Anders McD Sookermany, Cham: Springer, 2025, 48 chapters, ISBN 978-3-0300-2866-4.